Penguatan Literasi Numerasi Lintas Mata Pelajaran Bagi Guru Sekolah Menengah Pertama - Ulil Nurul Imanah; Deka Anjariyah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Numeracy is not only the responsibility of mathematics teachers, but also the responsibility of all non-mathematics teachers, namely teachers who teach subjects other than mathematics. The approach needed is cross-subject numeracy. Based on the results of interviews with partner schools, it was obtained that teachers in these schools still have minimal knowledge about numeracy literacy and numeracy reinforcement in non-mathematics lessons. The solution offered is to provide reinforcement of numeracy literacy materials and provide reinforcement of non-mathematics or cross-subject numeracy literacy materials so that non-mathematics teachers can also improve students' numeracy in subjects other than mathematics. The implementation mechanism consists of 3 main stages, namely the planning stage, the implementation stage, and the evaluation stage. Evaluation of program implementation is measured from the increase in participants' knowledge from pretest to posttest and the participant's response questionnaire to this activity. Based on the results of the community service, it can be concluded that this activity makes a good contribution to increasing the knowledge and understanding of SMP Terpadu Darul Dakwah teachers regarding cross-subject numeracy literacy and examples of learning activities to strengthen numeracy literacy in subjects other than mathematics. The number of participants who experienced an increase in score from pretest to posttest was 100%, meaning that all participants in the activity experienced an increase in knowledge. In addition, it can also be seen from the average pretest of 48 and the average posttest of 75.5. The overall process of implementing this activity went well and smoothly. This activity also received a positive response from the participants with a score percentage of 90.25%.